Pertanggungjawaban Hukum Penyalahgunaan Artificial Intelligence dalam Tindak Pidana di Indonesia: Kecerdasan Buatan - Junaidi, Junaidi; Fadzil, Rozlinda Mohamed; Vejasak, Tharin Phanuphong (UIR Law Review, 2026)
Basically, artificial intelligence (AI) is a program or machine created by humans that aims to mimic human abilities in various types of tasks. Considering that Indonesia does not yet have specific regulations regarding AI, the ability of AI to act like humans raises legal issues, especially when AI commits criminal acts that harm others. The research method used is normative juridical research, which employs a statutory approach and a conceptual approach. Laws and regulations related to the subject of the research are evaluated through a legislative approach. The analysis results show that AI can only be considered as a legal object in Indonesian positive law. Humans are absolute legal subjects and possess awareness and intent in actions carried out through AI, the creators and users of AI are responsible for AI's actions in criminal law